BIOLOGICAL ROLE OF THE ESSENTIAL MAJOR AND MICROELEMENTS, DISORDERS OF THEIR HOMEOSTASIS DURING PYELONEPHRITIS AMONG CHILDREN - E.G. Kuznetsova; R.R. Shilyaev; O.Yu. Fadeeva (Педиатрическая фармакология)
The disorders of the major and microelements exchange constiatute one of the pathogenic bases for formation of the nephritic pathology among children. the review deals with the information on the biological role and disorders of homeostasis of the most wellastudied essential major and microelements (zinc, magnesium, copper, iron) during pyelonephritis among children.Key words: major and microelements, kidneys, pyelonephritis, zinc, magnesium, copper, iron, children.